P.59: New Synthesis of Novel Phosphor for LED Technology: Synthesizing Sr3Y2(BO3)4:Eu2+ From Strontium Borate Precursors. Issue 1 (1st July 2013) - Kilburn, Troy B.; Way, Zachary K.; Orme, Patrick; Diaz, Anthony L.
Abstract: Doping Eu 2+ is challenging in some materials because of the stability of Eu 3+ . An alternative method for doping divalent europium was explored in the phosphor Sr3 B2 O6 :Eu. Sr3 B2 O6 :Eu has been synthesized with a mixture of divalent and trivalent emission. Here, samples prepared by traditional‐methods are compared to samples prepared using a SrB4 O7 :Eu precursor.